Satirical Television Programs and Their Impact on the Image of Iraqi Politicians - Abdul Ameer, Ameer Ali; Dheyab, Talib Abd ALmajeed (ALBAHITH ALALAMI, 2023)
This research delves into the role of satirical television programs in shaping the image of Iraqi politicians. The research problem is summarized in the main question: How does satire featured in television programs influence the portrayal of Iraqi politicians? This research adopts a descriptive approach and employs a survey methodology. The primary data collection tool is a questionnaire, complemented by observation and measurement techniques. The study draws upon the framework of cultural cultivation theory as a guiding theoretical foundation. A total of 430 questionnaires were disseminated among respondents who regularly watch satirical programs, selected through a multi-stage random sampling procedure. The researcher arrived at several key findings, including: A majority of the surveyed audience perceives the image crafted of Iraqi politicians through satirical programs as predominantly negative. A smaller portion of respondents believe that satirical programs do not offer a clear image of Iraqi politicians. Additionally, most respondents point to the portrayal of Iraqi politicians’ inability to deliver services to citizens as a prominent negative trait accentuated by satirical programs. These programs tend to omit any portrayal of positive attributes or the stances of politicians who prioritize upholding the Iraqi constitution.